Innate powers of togetherness and their development - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 2003)
The aim of the research is the effort to partly patch the holes of today school practice of education for full life. Due to the communicative action of children and adults one strives here to show how pedagogical methods with the quality of coexistence can be reached. The following research methods are used: narration of the event, phenomenological analysis of today’s educational reality. The article has four parts: 1) society - the phenomenon of partnership; 2) the discipline in the communicative act – the base of education; 3) the maturity of the communicative action – the condition of normal life; 4) diagnostics of communication phenomena, tasks and methods of education of communication skills. At first one describes the consolidation of being together with the characteristics of the partnership, the livelihoods, gender attraction, and love. The family is the duty of education of the values of coexistence. The discipline in the communicative act is here presented as maintenance, supervision, education. In other parts one analysis for important tasks to form the best features of the personality that is able to make a good life. At the end of the letter shows you different forms and methods of communication that best possibilities the togetherness of people.